Secretory Carcinoma of Male Breast: Case Report and Review of the Literature. (17th January 2011) - Gabal, S.; Talaat, S.
Abstract : Secretory carcinoma is a rare low-grade breast carcinoma, initially termed "juvenile breast cancer, " but it is now known to occur in adults of both sexes. It is the only epithelial tumor of the breast with a balanced translocation, t(12;15), that creates an ETV6-NTRK3 gene translocation. In this paper, a 19-year-old male patient has had a right breast mass for 9 years which suddenly increased in size with no evidence of palpable axillary lymph nodes. The mass was excised for frozen section and was diagnosed as malignant growth for simple mastectomy. Microscopic examination revealed the classical features of secretory carcinoma. The tumor cells were positive for EMA and S-100 protein and focally positive for cytokeratin and ER but negative for progesterone receptor, CD34, and CEA. Four months later the patient developed ipsilateral axillary lymph node enlargement, with lymph node metastases in five of the dissected 19 lymph nodes. The patient was treated with six courses of chemotherapy and radiotherapy. Conclusion . Though considered an indolent neoplasm, secretory carcinoma does metastasize to lymph nodes. Surgery in the form of mastectomy with axillary clearance is the treatment of choice. This paper includes a rare case report of secretory carcinoma in young male patient, with axillary lymph node metastasis in spite of the indolent nature that this tumor is known to display.